Framing the Decision: An Experimental Study on Managerial Judgements Post-Leadership Training - Aksoy, Yasin; Sahinkoc, Ender Mehmet (European Scientific Journal, ESJ, 2025)
This study was designed to contribute to the literature on behavioral economics and managerial psychology by investigating the influence of cognitive biases on decision-making processes. The research experimentally examines how managerial investment decisions may vary when identical market information is framed positively or negatively (framing effect). The study involved a total of 45 managers employed at a university. Participants first received a four-hour leadership training and were then randomly divided into two groups. Each group was presented with identical investment content, but framed differently. One group received information emphasizing investment opportunities (positive framing), while the other was exposed to risk- and uncertainty-oriented expressions (negative framing). Participants were asked to respond to the question “Should the company enter the market under these conditions?” with a simple “yes” or “no” and provide a brief justification for their decision. The quantitative findings revealed no statistically significant difference between the positively and negatively framed groups (χ² ≈ 0.045, p > .05). However, content analysis of open-ended responses showed that the underlying arguments were shaped in a frame-sensitive manner. While the positive framing group focused on opportunity-oriented reasoning, the negative framing group emphasized risk avoidance themes. These results are consistent with Tversky and Kahneman’s (1981) prospect theory and Loewenstein’s (2001) risk-as-feelings hypothesis. Furthermore, the leadership training appears to have mitigated the framing effect. The study highlights the impact of cognitive awareness and presentation style on managerial decisions and provides important evidence suggesting that such cognitive biases can be reduced through training.